TINGKATKAN PERILAKU HIDUP BERSIH DAN SEHAT DALAM MENGHADAPI NEW NORMAL PADA SISWA - Indah Dewi Ridawati; Nadi Aprilyadi; Zuraidah Zuraidah; Jhon Feri; Wella Juartika (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT, POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN PALEMBANG, 2021)
The number of sufferers and deaths due to the COVID-19 virus is increasing both in Indonesia and various countries in the world. PHBS (Clean and Healthy Living Behavior) health protocol education in the community really needs to be improved as an effort to prevent the spread of the corona virus. The purpose of this community service is to increase PHBS knowledge in facing the new normal period at SMPIT Al Qudwah, Musi Rawas Regency. The method of implementing activities online is through the zoom application. Participants fill out a Pre-Test using the google form application before the activity takes place and a Post Test immediately after the activity takes place. The community service participants were 42 grade IX students. The result of this activity was an increase in PHBS knowledge among students of SMP IT AL-QUDWAH, Musi Rawas Regency.